A review of the Neotropical Tirathabini genus Xenophasma Dognin, 1905 with description of two new species (Lepidoptera: Pyralidae, Galleriinae) - V. O. Becker (SHILAP)
Three species of Xenophasma Dognin, 1905, are recognized from Brazil, two of them new: Xenophasma albifasciata Becker, sp. n. and X. loxogramma Becker, sp. n., described here. Diagnosis, key to species, and illustrations of the type and two new species are also presented.